KREATIVITAS GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SDS IT AL-FURQON TEBAS - Ridho Afriandi; Suriadi; Parni (CV. ADIBA AISHA AMIRA, 2026)
This study aimed to describe teachers’ creativity in improving fifth-grade students’ learning motivation in the Pancasila Education subject at SDS IT Al-Furqon Tebas for the 2025–2026 academic year and to identify students’ learning motivation after the implementation of various learning methods. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The findings revealed that teachers’ creativity was implemented through the use of picture media, comics, and role-playing methods in Pancasila Education learning activities. These varied learning methods created a more engaging, active, and enjoyable classroom atmosphere. Furthermore, the use of creative learning methods increased students’ enthusiasm and learning motivation in participating in Pancasila Education classes. Therefore, teacher creativity plays an important role in enhancing students’ learning motivation in elementary schools.